Multinomial Regression with Elastic Net Penalty and Its Grouping Effect in Gene Selection - Liuyuan Chen; Jie Yang; Juntao Li; Xiaoyu Wang (Abstract and Applied Analysis)
For the multiclass classification problem of microarray data, a new optimization model named multinomial regression with the elastic net penalty was proposed in this paper. By combining the multinomial likeliyhood loss and the multiclass elastic net penalty, the optimization model was constructed, which was proved to encourage a grouping effect in gene selection for multiclass classification.